Astaxanthin protects against renal fibrosis through inhibiting myofibroblast activation and promoting CD8+ T cell recruitment - Diao, Wenli; Chen, Wei; Cao, Wenmin; Yuan, Hui; Ji, Hao; Wang, Tianwei; Chen, Wei; Zhu, Xingxing; Zhou, Hong; Guo, Hongqian; Zhao, Xiaozhi (Biochimica et biophysica acta. General subjects, 2019)
Renal fibrosis is a common pathological hallmark of chronic kidney disease, and no effective treatment is clinically available to manage its progression. Astaxanthin was recently found to be anti-fibrotic, but its effect on renal fibrosis remains unclear. C57BL/6J mice were subjected to unilateral ureteral obstruction and intragastrically administered astaxanthin. Histopathology and immunohistochemistry were performed to evaluate renal fibrosis. Flow cytometry was used to examine lymphocyte accumulation in the fibrotic kidneys. Western blotting, real-time qPCR, and immunofluorescence were performed to cover the underlying mechanism concerning astaxanthin treatment during renal fibrosis. Oral administration of astaxanthin effectively alleviates renal fibrosis in mice. In vitro, astaxanthin inhibited fibroblast activation by modulating Smad2, Akt and STAT3 pathways and suppressed epithelial-to-mesenchymal transition in renal tubular epithelial cells through Smad2, snail, and β-catenin. Moreover, astaxanthin significantly induced the rapid accumulation of CD8+ T cells in fibrotic kidneys, which was accompanied by elevated expression of IFN-γ. Accordingly, the depletion of CD8+ T cells strongly diminished the protective effect of astaxanthin. Further investigation showed that astaxanthin increased the population of CD8+ T cells by upregulating the expression of CCL5 in macrophages. These findings highlight the beneficial effect of astaxanthin on fibroblast activation, epithelial-to-mesenchymal transition, and CD8+ T cell recruitment during renal fibrosis. These data indicate that astaxanthin could serve as a therapeutic strategy to treat renal fibrotic conditions. •Astaxanthin exhibited marked protective effects against renal fibrosis.•It inhibited fibroblast activation via Smad2, Akt, and STAT3.•It suppressed EMT in tubular epithelial cells via Smad2, snail, and β-catenin.•It promoted the accumulation of IFN-γ-expressing CD8+ T cells in the kidney.•To recruit CD8+ T cells, it upregulated the expression of CCL5 in macrophages.